2014
DOI: 10.7235/hort.2014.14027
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Cucurbits to Podosphaera xanthii Race 1

Abstract: This study was conducted to establish an efficient screening method to identify cucurbits resistant to powdery mildew. Powdery mildew fungus was obtained from a single lesion of infected cucumber leaf in 2010 at Daejeon. The fungus was identified as Podosphaera xanthii race 1 based on morphological characteristics and resistance responses of four melon differentials. Development of powdery mildew caused by the fungal isolate on 34 commercial cultivars of cucumber was investigated at three plant growth stages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although a few studies have identified the causal fungi of powdery mildew in watermelon in Korea (Lee et al, 2010;Kim et al, 2013;Lee et al, 2014), we attempted to characterize the genera and races of the pathogen using previously reported methods for other crops (Bardin et al, 1999;Chen et al, 2008) based on morphological and molecular characters. All morphological characters of the conidia, including the shape, size, and the presence of fibrosin bodies, matched those of P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies have identified the causal fungi of powdery mildew in watermelon in Korea (Lee et al, 2010;Kim et al, 2013;Lee et al, 2014), we attempted to characterize the genera and races of the pathogen using previously reported methods for other crops (Bardin et al, 1999;Chen et al, 2008) based on morphological and molecular characters. All morphological characters of the conidia, including the shape, size, and the presence of fibrosin bodies, matched those of P.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, 23 cultivars out of 120 watermelon accessions showed moderate resistance to powdery mildew (Lee et al, 2010). In another trial, 51 commercial cultivars of cucumber (Cucumis sativus), melon (Cucumis melo), and watermelon were screened for resistance to P. xanthii race 1, but this strain was not pathogenic on tested watermelon cultivars (Lee et al, 2014). The authors suggested that the tested P. xanthii race 1 that is infectious to cucumber and melon does not correspond to race 1W, which is infectious to watermelon.…”
Section: Introductionmentioning
confidence: 99%
“…, Zitter (1996) race race 1 (Table 1). P. xanthii race race 1 (Zitter et al, 1996), race (Kim , 2016;Lee , 2014). MR-1 6.9% (R) (Fig.…”
Section: P Xanthii Racementioning
confidence: 99%
“…(Pirondi , 2015) internal transcribed spacer (ITS) ITS1 (5 -TCCGTAGGTGAACCTGCGG-3 ) ITS4 ( 5-TCCTCCGCTTATTGATATGC-3 ) (polymerase chain reaction) . (Lee , 2014).…”
Section: Ki170723 Gw170710 Se180328 Mi180427mentioning
confidence: 99%
See 1 more Smart Citation